Exposure of the euro area's financial sector to risk coming from Russia, China, and the Middle East - Katja Ahoniemi; Eeva Kerola; Kimmo Koskinen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
This paper examines the current dependencies and exposures of the euro area's financial sector in a context of rising geopolitical tensions. Focusing on Russia, China, and the Middle East, we analyze direct exposures through lending and securities holdings of banks and large investors. Our findings suggest that the already modest exposures of the euro area have decreased in recent years. Notably, euro area banks and investors have significantly reduced their exposure to Russia in the wake of the Ukraine invasion, and China in response to regulatory uncertainty. Euro area banks reacted quickly to heightened geopolitical risk in the Middle East by reducing their exposure to countries affected by recent turmoil. A new set of potential risks have emerged, however, as a result of strengthened financial ties with the United States.
urn:nbn:fi-fe2025021412134
Keywords: 330; Geopolitical tensions; financial exposure; banking sector; China; Russia; Middle East